2017
DOI: 10.1111/opo.12379
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of portable electronic and optical magnifiers for near vision activities in low vision: a randomised crossover trial

Abstract: The study provides evidence that p-EVES devices can play a useful role in supplementing the range of low vision aids used to reduce activity limitation for near vision tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
0
22
0
2
Order By: Relevance
“…In the U.K., research has found portable electronic magnifiers to be the device of choice for leisure reading in experienced optical magnifier users, and a cost-effective supplement to optical devices. 10,11 Together, these findings support the importance of electronic magnifier provision, even in a setting with limited financing.…”
Section: Discussionmentioning
confidence: 54%
“…In the U.K., research has found portable electronic magnifiers to be the device of choice for leisure reading in experienced optical magnifier users, and a cost-effective supplement to optical devices. 10,11 Together, these findings support the importance of electronic magnifier provision, even in a setting with limited financing.…”
Section: Discussionmentioning
confidence: 54%
“…This is probably due to the fact that optical magnifier with higher magnification power restrict the field of vision distinctively. Besides that, p-EVES allow handling in habitual distance and better contrast [43]. Despite that, all patients could read fastest with CCTV.…”
Section: Discussionmentioning
confidence: 99%
“…In another crossover study comparing the near vision activity performance of 84 experienced users of optical aids when using portable electronic vision enhancement systems plus optical magnifiers or optical magnifiers alone, it was observed that, at 2 months, the use of electronic systems allowed longer duration of reading. In addition, participants reported less difficulty performing a range of near vision activities when using these systems and were able to perform more tasks independently [70].…”
Section: Electronic Aidsmentioning
confidence: 99%